2016
DOI: 10.1111/wej.12210
|View full text |Cite
|
Sign up to set email alerts
|

Combining magnesium ammonium phosphate precipitation with membrane processes for ammonia removal from methanogenic leachates

Abstract: Chemical precipitation of ammonia as magnesium ammonium phosphate (MAP) from methanogenic leachates can be a competitive alternative to biological ammonia removal. Potential for trading of the precipitate as a fertiliser defines the economics of the process. The precipitate from a landfill leachate often containing organics and heavy metals as impurities with unknown risks limits its possibility for agricultural use. This study combines MAP precipitation with membrane processes and investigates the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Nanofiltration placed before reverse osmosis can provide greater flexibility for ammonia removal, since the organic compounds can be selectively separated. Ramaswami et al [ 35 ] reported the ability to recover ammonia from nanofiltration permeate of raw leachate as clean and useable struvite, which can be sold as a fertilizer. Since organics and hardness contents in the NF permeate are low, stripping of ammonia from RO retentate of NF permeate can be accomplished without significant foaming and scaling problems, which is often faced during ammonia stripping from leachates [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanofiltration placed before reverse osmosis can provide greater flexibility for ammonia removal, since the organic compounds can be selectively separated. Ramaswami et al [ 35 ] reported the ability to recover ammonia from nanofiltration permeate of raw leachate as clean and useable struvite, which can be sold as a fertilizer. Since organics and hardness contents in the NF permeate are low, stripping of ammonia from RO retentate of NF permeate can be accomplished without significant foaming and scaling problems, which is often faced during ammonia stripping from leachates [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the Ihlenberg landfill, the raw leachate (see composition in Table 2 ) gets about five times concentrated by the two-stage reverse osmosis (about 30, 15, 4, and 3 g/L Cl − , Na + , TOC and NH 4 + -N, respectively, in RO retentate). For this scenario for instance, biological treatment of RO retentate or its NF permeate would be challenging due to high salinity and the purity of struvite precipitated from the NF permeate of RO-NF would be lower [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main environmental problems arising during solid waste landfilling is the generation of heavily polluted landfill leachates [3]. They are highly loaded wastewater containing a wide variety of pollutants, including organic compounds, heavy metals and inorganic salts [1,[3][4][5]. The concentration of most components in landfill leachate exceed the concentration of the same in the sewage sludge [2].…”
Section: Introductionmentioning
confidence: 99%
“…), energy in the water sector (McNabola ) and engineered treatment systems (Patziger & Kiss ; Ramaswami et al . ). Our proposition is to refresh the ambition of the journal to re‐emphasise this unique contribution, whilst also launching several new publication initiatives in support of this vision.…”
mentioning
confidence: 97%